Management of Haemophilia in Greece - Mandalaki, T (Thrombosis and Haemostasis, 1976)
A short review is given on several aspects of the management of haemophilia in Greece. A total number of 429 patients with congenital haemorrhagic disorders has been registered. The incidence of F. VIII deficiency is 85.9% and that of F. IX 12.9%. Information concerning distribution throughout the country, age, social standard, financial position and education is given too.Haemophiliacs are systematically treated by Athens specialized Haemophilia Treatment Centres.The most widely therapeutic material still used, is fresh frozen plasma. Lyophilized cryo-precipitate and F. IX (prothrombincomplex) concentrate are also prepared but they are not for every day use. Imported concentrates are used only for very serious cases.Home therapy is attempted in limited scale and it is largely discussed.Consultation, out-patients treatment and hospitalization, if needed, are free of charge for haemophiliacs regardless of their financial position or their national insurance.